MONITORING PENGAMAN BANGUNAN MENGGUNAKAN SENSOR GERAK BERBASIS MIKROKONTROLLER ATMEGA8535 - Samsul; Bambang Supradono; Luqman Assaffat (MEDIA ELEKTRIKA, 2016)
Safety of storeroom is absolutely needed by every company. If there is a safe feeling, the company will not be afraid of. To reduce an afraid, it is designed a device of Monitoring safetystoreroom by using Movement Sensor ATMEGA8535 Microcontroller -based. In this last project, the writer makes that device equipped with PIR sensor which is put in the corner of the storeroom. As its process equipment, it is used ATMEGA8535 microcontroller as program centre. Then, the work method of output appearance as dot matrix, buzzer and bulb lamp is PIR sensor will detecthuman existence or not at the time of storeroom in empty situation. Furthermore, ATMEGA8535 microcontroller sends output signal through dot metric as the direction of storerooms location. After that, buzzer is as alarm and bulb lamp is as indicator lamp. Besides, reset knob is function as system reset when dot matrix, buzzer, and bulb lamp ON. Base on the research data, PIR sensor range is Horizontally about 300-1500 detected. Then, range data of PIR sensor is Vertically with Elevation and Depression which is detected. Furthermore, research data of PIR sensor is based on range 0.5-5.5 meters detected. Key words: Monitoring equipment, PIR KC7783R sensor, ATMEGA8535 microcontroller, dot matrix, buzzer, bulb lamp